The Effect of Advertising and Brand Image on the Buying Interest of Lion Air Airline Passengers at Tjilik Riwut Airport, Palangka Raya, Central Kalimantan - Enjellica Rivera; Desiana Rachmawati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Having a strong brand image is a must for every company because corporate image is the most valuable asset. A strong brand image can develop a corporate image by carrying the company name. A positive brand image will create a good impression on the minds of passengers in consuming a brand. One impressed form of a brand image is PT. Sea lion. Knowing the partial effect of advertising on the buying interest of Lion Air airline passengers at Tjilik Riwut Palangka Raya Airport. Knowing the effect of brand image partially on the buying interest of Lion Air airline passengers at Tjilik Riwut Palangka Raya Airport. Knowing the influence of advertising and brand image simultaneously on the buying interest of Lion Air airline passengers at Palangka Raya Airport. This research is a quantitative research, data sources used are primary data and secondary data. This research was conducted on 25 February - 10 March 2023 and was carried out at Tjilik Riwut Airport in Palangka Raya, Central Kalimantan. The population in this study were passengers who used Lion Air services through Tjilik Riwut Palangka Raya Airport. The total population in this study is 9,893,130 passengers in 2021. With a research sample of 100 using the simple random sampling technique. Data collection techniques are surveys, literature studies, research instruments. The research instrument test is the validity test and reliability test. Data analysis tests used in this study include: classical assumption test and hypothesis testing, hypothesis testing consists of multiple linear regression tests, T tests, F tests, and tests of the coefficient of determination. Based on the results of the data that has been processed by researchers in this study, it is concluded that H1 is accepted, meaning that there is a significant partial effect between the advertising variable (X1) on purchase intention (Y), H2 being rejected means that there is no influence of brand image variable (X2) on purchase intention ( Y) explains that brand image (X2) has no effect on purchase intention (Y), because if a company or airline only has attractive advertisements (X1) but does not have a good brand image in the eyes of passengers, it will not affect purchase intention (Y). , but if employees are exposed to advertising problems (X1) and brand image (X2) it will only affect purchase intention (Y), the results of the F Test simultaneously the advertising variable (X1) and brand image (X2) do have an influence on buying interest, and advertising and brand image variables have an influence of 0.571 or 57.1% on the buying interest of Lion Air airline passengers